Determinants of Government Apparatus Performance: The Perspective of Budget Participation, Public Accountability, and Supervision - Rapsanjani, Hilal; Paranoan, Selmita; Din, Muhammad; Yamin, Nina Yusnita (UNIVED Press, 2026)
This study aims to explain how budget participation, public accountability, and supervision together contribute to improving the apparatus performance, as well as expanding the object of study to Regional Apparatus Organizations (RAO) in other districts, both within the scope of Southeast Sulawesi and outside the province. The data were obtained through the direct distribution of questionnaires to respondents across 34 RAO. The data analysis method of choice was the structural equation modeling–partial least squares (SEM-PLS) approach. Software called SmartPLS 4.1 was used to process the data for this investigation. The outcomes of hypothesis testing demonstrate that budget participation, public accountability, and supervision each exert a positive and significant effect on the apparatus performance.